INDIGENCE OF FORENSIC ODONTOLOGY IN LEGAL PRACTICE OF PAKISTAN: Forensic Odontology - Mansoor, Hashim Bin; Kayani, Usman Zafar; Khatoon, Reeja; Idrees, Erum; Kayani, Hira Zafar; Aslam, Ayesha (Pakistan Armed Forces Medical Journal, 2021)
Objective: To assess and interpret the utility and need of forensic dentistry in current judicial system of Pakistan.Study Design: Cross sectional study.Place and Duration of Study: Twin cities of Rawalpindi and Islamabad, in the month of Jun, 2020.Methodology: This questionnaire based cross-sectional study was conducted in a 1-month time frame, and a sample of 100 lawyers was recruited using snowball sampling technique and only criminal lawyers were included which had a minimum of 5 years of experience. Data was analyzed using SPSS-24.Results: The results were quite significant, 81% (81 lawyers) of the population recognized the relationship of forensic dentistry with criminal litigation (p-value=0.006). Furthermore 86% (86 lawyers) believed that there are a limited number of practicing forensic dentists and a massive 96% (96 lawyers) of the population was not able to acquire the expertise of a forensic dentist.Conclusion: There is a major lack of trained forensic odontologists and training institutes in Pakistan, which has a significant effect on the legal practices of Pakistan. Furthermore, it defines the lack of specialization trend in forensic odontology.